Amplitude of hip and knee movement associated with body mass index in elderly (Research, Society and Development, 2021)
Objective: To check the range of hip and knee motion and the association with BMI in the elderly. Methodology: This is a bibliographic review bibliographic research, in the Google Academic databases, SciELO, LILACS and PUBMED in the period 2010 to 2020, where the PICO strategy was structured through the association of the descriptors. Results: Eight studies were included, with a prevalence of publications in the year 2013, of which 6 (75%) were publications in the Portuguese language, and 2 (25%) in the English language. The results indicate that the practice of physical exercise involving strength, mobility and flexibility improve physical fitness, body composition and range of motion (ROM) in the elderly, despite the age and body mass index (BMI) influence directly in the range of hip motion. Conclusion: It can be concluded that the aging process is individually located in each individual and may influence the BMI as well as other variables (age, environment, level of physical activity), and may interfere with the elderly parameters of the elderly, special in hip joint and physical activity has been an important ally in the acquisition or maintenance of this physical capacity.